Complex algorithm for identify the parameters of the navigation satellites and satellite navigation using the principle of inter-satellite measurements - S. V. Sokolov; V. V. Kamenskij; S. M. Kovalev; V. D. Meerovich (Известия высших учебных заведений России: Радиоэлектроника)
The solution of a problem of identification of the current coordinates of navigation satellites together with definition of errors of mutual synchronization of their hours directly onboard the satellite on the basis of use of simple methods of inter-satellite radio - and laser measurements is considered.